Three levels, two needs, one goal: Fostering an integrated sense of inclusion through inclusive leadership - Jona Wölk; Fabiola H. Gerpott; Rudolf Kerschreiter (Journal of Occupational and Organizational Psychology, 2025)
Employees' inclusion at work often constitutes a key leadership objective. Indeed, inclusive leadership has garnered considerable attention from research and practice, with differing interpretations persisting in the debate. An influential stream of research claims to ground its understanding of inclusive leadership in optimal distinctiveness theory (ODT), which states that people strive to fulfil two countervailing needs (i.e., assimilation and differentiation). Closer examination, however, reveals inaccuracies in applying ODT to inclusive leadership, leading to an incomplete set of proposed inclusive leader behaviours. To address these issues, we critically examine inclusive leadership's definition and theoretical foundation and propose a multi-level framework informed by the extended version of ODT (EODT). More specifically, we detail how three complementary sets of inclusive leader behaviours can foster an employee's integrated sense of inclusion by addressing the employee's needs for assimilation and differentiation at three levels of self (i.e., individual, relational, and collective). We argue that before engaging in these behaviours, a leader must reflect on their employee's, their own, and other team members' minority/majority status to effectively adapt their actions. We discuss future research implications of this multi-level perspective on an employee's self for broader team/social justice considerations and end with practical implications.
Keywords: 650; countervailing needs; diversity management; extended optimal distinctiveness theory; inclusion; inclusive leadership; inequality